The Association between Parental Religiosity, Stressful Life Events, and Problem Behavior in Pre- Adolescents and Adolescents - Van Der Jagt-Jelsma, Willeke; De Vries-Schot, Margreet R.; Klip, Helen; Van Deurzen, Patricia A.m.; Buitelaar, Jan K. (European Journal of Mental Health, 2019)
Objective: To investigate whether religiosity influences exposure to stressful life events (SLEs) and whether religiosity moderates the effects of SLEs, resulting in fewer problem behaviors.Method: The self-reported mental health problems of a community-based longitudinal sample of pre-adolescents (n = 2230) in the three northern provinces of the Netherlands were assessed in early adolescence (12-15 years, Youth Self-Report, YSR) and in adolescence (18-21 years, Adult Self Report ASR). The sum scores for SLEs in early adolescence were based on the previous two years. The variable parental religiosity was based on information obtained in pre-adolescence (10-12 years). Associations between religiosity and SLEs and whether parental religiosity is a moderator between SLEs and problem behaviors were studied, using repeated measures ANOVAs.Results: Having actively religious parents was associated with fewer SLEs. Parental religiosity did not moderate the association between SLEs and problem behavior. Conclusions: The children of actively religious parents experienced fewer SLEs in pre-adolescence than did the children of non-religious parents or the children of parents with incompatible religious beliefs, but parental religiosity did not moderate the effects of SLEs on problem behaviors. Reasons for the absence of a religious coping effect are discussed.